PERTANGGUNGJAWABAN DOKTER ATAS KESALAHAN DIAGNOSIS PADA PELAYANAN KLINIK ONLINE YANG DILAKUKAN MELALUI MEDIA ONLINE - Michael Josua Hisar Hutauruk; Chan Ogesdi Damanik; Yolanda Pratiwi; Sonya Airini Batubara (The Juris, 2021)
Advances in technology also have an impact in the health sector, namely telemedicine, which implies the existence of online-based health clinical services. In online-based health / medical services, it must also pay attention to the professional ethics of the workforce concerned, which must be based on awareness, responsibility and high morale in accordance with respective professional ethics. The relationship between doctors and patients who are balanced or equal in law is called a contractual relationship or can be called a therapeutic transaction. Juridically, therapeutic transactions are defined as the legal relationship between doctors and patients in professional medical services based on competencies in accordance with certain expertise and skills in the field of medicine, the services provided are the provision of help or assistance based on the patient's trust in doctors. However, it turns out that there are many malpractices committed by doctors to patients, causing many losses. However, legally, the follow-up on malpractice committed by doctors is not legally strong. This research uses legal normative research in which a process of finding a rule of law, legal principles, and legal doctrines in order to answer the legal issues at hand. The data collected is used with data research and related legal studies as well as analysis of existing data.